Certainty, But How Certain? Severity, But How Severe? A Quasi-Experimental Study on Digital Piracy Deterrence in a Spanish Citizens Sample - Gómez-Bellvís, Ana Belén (Crime & delinquency, 2025)
The assumptions underlying classical deterrence remain an underpinning of most legal systems. Although empirical research on deterrence is extensive, less investigated are the conditions under which deterrence is more or less likely to occur. The aim of this study is to analyze the influence of sanction severity and certainty on intentions to illegally download a film. A 3 × 4 factorial design was used in which three degrees of severity and 4° of certainty were combined. Results show that when low or medium certainty can be guaranteed, the degree of severity influences the intention to illegally download. However, severity is irrelevant when certainty is zero or total. These results suggest that severity is important, but its relevance is conditioned by the level of certainty.